New functions of C3G in platelet biology: Contribution to ischemia-induced angiogenesis, tumor metastasis and TPO clearance - Hernández-Cano, Luis; Fernández-Infante, Cristina; Herranz, Óscar; Berrocal, Pablo; Lozano, Francisco S.; Sánchez-Martín, Manuel A.; Porras, Almudena; Guerrero, Carmen (Frontiers in Cell and Developmental Biology, 2022)
C3G is a Rap1 guanine nucleotide exchange factor that controls platelet activation, aggregation, and the release of α-granule content. Transgenic expression of C3G in platelets produces a net proangiogenic secretome through the retention of thrombospondin-1. In a physiological context, C3G also promotes megakaryocyte maturation and proplatelet formation, but without affecting mature platelet production. The aim of this work is to investigate whether C3G is involved in pathological megakaryopoiesis, as well as its specific role in platelet mediated angiogenesis and tumor metastasis. Using megakaryocyte-specific C3G knockout and transgenic mouse models, we found that both C3G overexpression and deletion promoted platelet-mediated angiogenesis, induced by tumor cell implantation or hindlimb ischemia, through differential release of proangiogenic and antiangiogenic factors. However, only C3G deletion resulted in a higher recruitment of hemangiocytes from the bone marrow. In addition, C3G null expression enhanced thrombopoietin (TPO)-induced platelet production, associated with reduced TPO plasma levels. Moreover, after 5-fluorouracil-induced platelet depletion and rebound, C3G knockout mice showed a defective return to homeostatic platelet levels, indicating impaired platelet turnover. Mechanistically, C3G promotes c-Mpl ubiquitination by inducing Src-mediated c-Cbl phosphorylation and participates in c-Mpl degradation via the proteasome and lysosome systems, affecting TPO internalization. We also unveiled a positive role of platelet C3G in tumor cell-induced platelet aggregation, which facilitated metastatic cell homing and adhesion. Overall, these findings revealed that C3G plays a crucial role in platelet-mediated angiogenesis and metastasis, as well as in platelet level modulation in response to pathogenic stimuli.